Examining the direct and indirect effect that individual and contextual risk factors have in predicting substance abuse - Fouten, Elron Steve (Rhodes University, Faculty of Humanities, Department of Psychology)
Substance abuse levels in South Africa have continued to rise, with the age of first experimentation with drugs reported as being 10 years. Several studies have shown that substance abuse has an adverse impact on users, their families and their communities, resulting in a number of social, psychological and economic struggles. Moreover, substance abuse places an increased psychological, social and financial burden on the individual and the family, as it has been related to the destabilisation of the nuclear and extended family units, permeating every area of life and affecting the very social fabric of society. This study therefore endeavoured to determine which of the individual and contextual risk factors measured by the South African Substance Use Contextual Risk Instrument (SASUCRI) best predicts substance abuse in a sample of self-identified substance abusers. Additionally, the study sought to determine the magnitude, strength and direction of the interaction of the individual and contextual risk factors in predicting substance abuse. The specific aims of the study were: 1) to build a theoretical model that best approximates the identified and measured individual and contextual factors associated with substance abuse, 2) to use structural equation modelling (SEM) to test the adequacy of the model's fit to the data that have been collected, 3) to use SEM to statistically determine which of the perceived individual or contextual factors best predict substance abuse, and 4) to use SEM to statistically determine which combination of perceived individual and contextual factors best predict substance abuse. To achieve these aims, the study applied SEM to data collected from individuals seeking either inpatient or outpatient treatment for substance abuse in the Eastern Cape and Western Cape Provinces of South Africa, respectively. The purpose of SEM is to a priori specify a theoretical causal model consisting of a set of predicted covariances between variables, and then test whether it is plausible when compared to the observed data. The appropriateness of performing SEM exists in its ability and suitability to examine the nature and magnitude of postulated dependence relationships, while simultaneously assessing the direct and indirect relations of the variables. The theoretical causal model that was tested contained latent and manifest variables that were identified as risk factors for substance abuse. The causal model was informed by Bronfenbrenner's (1977a, 1986) ecological systems theory (EST) and was specified to approximate the different systems of the theory. Data for the study were collected using the relatively newly developed and validated SASUCRI. The results of the confirmatory factor analysis (CFA) showed that the SASUCRI was a reliable and valid instrument to use with this population, and that the results of the structural model can be interpreted with confidence. The fit statistics, for the normal theory and related bootstrap latent path SEM, all indicate that the model is an excellent fit to the data CMIN/DF = 2.82, NFI = .946, CFI = .97, RMSEA = .04., thus achieving the study's objective. The normal theory analysis of the paths in the diagram identified the microsystem, "Access/proximity to drugs" (APTD) and "Concerns for future" (CFF) as significant predictors of substance abuse, whereas the bootstrap analysis of the paths identified the macrosystem, APTD and CFF as significant predictors of substance abuse. This study identified 10 risk profiles that interact in the prediction of substance abuse; these are: individuals with low self-efficacy (SE) who perceive their family as lacking or having low intra-family communication, who lack positive peer support, who perceive criminal behaviours as normal, who feel a strong need to fit in, who are less religious, who have easy access to drugs, who lack a sense of community traditions and belonging, who see public displays of substance use (SU) as normal, and who lack concern for the future, are at 59% greater risk of substance abuse. Though micro level factors (low SE, lack of or low intra-family communication, and a lack of positive peer support) and meso-level factors (normalisation of criminal activity, a strong need to fit in, and being less religious) does not significantly predict abuse, they significantly interact with external factors in predicting substance abuse. Thus, it is only when they interact with factors located in the other systems (exosystem, macrosystem and chronosystem) that they become significant predictors of substance abuse. Conversely, exosystem (easy access to drugs), macrosystem (lack of a sense of community traditions and belonging, commonplace public displays of SU), and chronosystem factors (lack of concern for the future), independently are significant predictors of substance abuse. These findings carry significant public health implications by challenging the prevailing focus on individual-based interventions. Recognising that the drivers of substance abuse extend beyond individual factors, this study therefore advocates for interventions that address the broader systems contributing to the issue. This has the potential to inform more effective and holistic public health strategies. Finally, this study emphasises the need for comprehensive strategies that span different systems, acknowledging the role of family, community and societal factors. This call for complex interventions aligns with the ecological systems perspective, advocating for a paradigm shift in how we address SU by considering the broader environmental influences that contribute to the problem. In summary, this study not only contributes to the academic understanding of SU, but also has practical implications for public health policies and interventions.
Keywords: Structural equation modeling; Substance abuse -- South Africa; Ecological Systems Theory; Path analysis (Statistics); Personality; Confirmatory factor analysis